Cell culture systems for isolation of SARS-CoV-2 clinical isolates and generation of recombinant virus - Chen, Da-Yuan; Turcinovic, Jacquelyn; Feng, Shuchen; Kenney, Devin J.; Chin, Chue Vin; Choudhary, Manish C.; Conway, Hasahn L.; Semaan, Marc; Close, Brianna J.; Tavares, Alexander H.; Seitz, Scott; Khan, Nazimuddin; et al. (iScience, 2023)
A simple and robust cell culture system is essential for generating authentic SARS-CoV-2 stocks for evaluation of viral pathogenicity, screening of antiviral compounds, and preparation of inactivated vaccines. Evidence suggests that Vero E6, a cell line commonly used in the field to grow SARS-CoV-2, does not support efficient propagation of new viral variants and triggers rapid cell culture adaptation of the virus. We generated a panel of 17 human cell lines overexpressing SARS-CoV-2 entry factors and tested their ability to support viral infection. Two cell lines, Caco-2/AT and HuH-6/AT, demonstrated exceptional susceptibility, yielding highly concentrated virus stocks. Notably, these cell lines were more sensitive than Vero E6 cells in recovering SARS-CoV-2 from clinical specimens. Further, Caco-2/AT cells provided a robust platform for producing genetically reliable recombinant SARS-CoV-2 through a reverse genetics system. These cellular models are a valuable tool for the study of SARS-CoV-2 and its continuously emerging variants. [Display omitted] •Human cell lines overexpressing ACE2 and TMPRSS2 were tested for SARS-CoV-2 infection•Two cell lines, Caco-2 and HuH-6, exhibited remarkable susceptibility to infection•Caco-2 and HuH-6 cells allowed isolation of SARS-CoV-2 from clinical specimens•Caco-2 cells supported production of genetically stable recombinant SARS-CoV-2 Methodology in biological sciences; Virology